Performance and plume characterization of a laboratory krypton Hall thruster - Andreano, Thomas Malachi, author; Williams, John D., advisor; Marchese, Anthony J., committee member; Roberts, Jacob L., committee member (Colorado State University. Libraries, 2020)
Hall thruster research has been in progress at the CSU Electric Propulsion and Plasma Engineering (CEPPE) lab for the past decade, however, a full performance and plasma plume characterization has not been conducted with the laboratory Hall thruster available, which recently was modified to be configured as magnetically shielded as well as non-magnetically shielded. Additionally, heaterless cathode geometries that could benefit scaling of Hall thrusters to either much larger or much smaller designs have been undergoing development at the CEPPE lab. One of these cathodes, named the postage stamp, was designed to mount to the outer pole piece on the front of the thruster in the seperatrix of the magnetic field, and fits in the space between the outer pole piece and the backplate of the thruster. To further the research on Hall thrusters at CSU, a baseline of the laboratory thruster performance is necessary, and performance characterization of the operation using different cathodes is necessary to further the cathode design. To these ends, performance of the thruster was characterized with: (1) the center mounted cathode, providing a baseline for all future Hall thruster research at the CEPPE lab, (2) with the postage stamp cathode, to determine the potential performance differences between operation with the two cathodes, and (3) in the magnetically shielded configuration, to verify proper operation and investigate any potential performance differences compared to the traditional configuration. Thrust measurement, along with data from an Electrostatic Analyzer (ESA), ExB probe, and Faraday probe were collected to determine the performance characteristics of the thruster as well as the characteristics of the ion beam in each of the three cases outlined above. Additionally, a preliminary study of an anomalous operation mode providing higher than usual performance was conducted using these probes, as well as a combined ESA/ExB called the EVADER probe.
Keywords: Hall thruster; propulsion; electric propulsion; space; plasma